Association between advance care planning and depressive symptoms among community-dwelling people with dementia: An observational cross-sectional study during the COVID-19 pandemic in Japan - Nakanishi, Miharu; Nakashima, Taeko; Miyamoto, Yuki; Sakai, Mai; Yoshii, Hatsumi; Yamasaki, Syudo; Nishida, Atsushi (Frontiers in Public Health, 2023)
Objectives Advance care planning (ACP) is an increasing priority for people with dementia during the COVID-19 pandemic. This study evaluated the association between ACP initiation and depressive symptoms among home-dwelling people living with dementia. Methods An internet-based questionnaire survey was conducted with Japanese family caregivers of home-dwelling persons with dementia in June 2021. Family caregivers evaluated the level of depressive symptoms in persons with dementia using the Neuropsychiatric Inventory (NPI). Caregivers also rated the quality of life of persons with dementia using the EQ-5D-5L. Results A total of 379 family caregivers participated in the survey. Depressive symptoms were reported in 143 persons with dementia (37.7%). A total of 155 persons with dementia (40.9%) had initiated ACP, of which 88 (56.8%) had care professionals involved in ACP conversation. After adjusting for the characteristics of persons with dementia and caregivers, persons with professional involvement showed significantly more severe depressive symptoms compared to those who did not initiate ACP. There was no significant difference in the quality of life of persons with dementia according to ACP initiation. Conclusions Many home-dwelling persons with dementia experienced depressive symptoms during the COVID-19 pandemic, especially in cases where care professionals were involved in ACP conversations. Optimal and proactive ACP approaches need to be developed to prevent depressive symptoms in newly diagnosed persons.